Cowpea (Vigna unguiculata) Extract Reduce Malondialdehyde Levels and Prevent Aortic Endothelial Cell Decline in Ovariectomized Rats - Ni Putu Sri Haryati; Elisa Danik Kurniawati; Tanti Tri Lestary; Eviana Norahmawati; I Wayan Arsana Wiyasa; Dwi Yuni Nur Hidayati; Tatit Nurseta (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2021)
Estrogen has anti-oxidative and anti-inflammatory properties, but its levels decrease in postmenopausal women who can trigger oxidative stress. One of the most damaging effects of ROS is lipid peroxidation, and the end product is Malondialdehyde (MDA). Similarly, aging endothelium has increased oxidative stress and endothelial cell sensitivity to apoptosis. This study aimed to determine the effect of cowpea extract on serum MDA levels, aortic endothelial cell counts, and brain MDA levels in the ovariectomy model. Cowpea extract can be used as an alternative to prevent and overcome the effects that occur during menopause, such as cardiovascular problems, decreased bone mineral density, and dementia. The study used 15-month-old female Rattus norvegicus, divided into six groups (OVX, SHAM, OVX+estradiol, OVX+Vu 1.25; 2.5; and 5 mg/kg BW/day). Serum and brain MDA levels were examined by ELISA method, while the number of aortic endothelial cells were examined on histopathological preparations with Hematoxylin & Eosin (HE) staining. The mean value of serum and brain MDA levels decreased with an increase in the dose given (p-value 0.016). The mean value of aortic endothelial cells between the dose groups did not significantly differ. However, the mean value showed an increasing trend as the dose of cowpea extract was given. The results of this study indicate that the extract of cowpea has the potential as an antioxidant to reduce serum and brain MDA levels, prevent a decrease in the number of aortic endothelial cells. As prevention, cowpea extract can be used as an antioxidant and consumed since premenopause to minimize problems that occur during postmenopause.